Lebanon Pasca Ledakan Beirut Tahun 2020 - Kusumawandira, Irawanti Ayu (Jurnal ICMES, 2022)
The Beirut Explosion tragedy in 2020 occurred at a time when Lebanon was experiencing a multifaceted crisis such as economic, political, and health crisis. The impact of this tragedy placed the Lebanese people in a great humanitarian crisis. This article aims to identify the threat to human security that emerged as a result of the tragedy and to see how the international community provided humanitarian aid to Lebanon. By using qualitative research methods and literature study, the authors found that all dimensions of human security have been threatened. These dimensions include food security, political security, economic security, health security, environmental security, personal security, and community security. The international community consists of state actors, international organizations such as UN agencies, companies, and individuals who work together to provide humanitarian assistance to Lebanese citizens. The existence of assistance and aid such as the provision of health facilities, education, housing, food, and cash in the long term from each party has been able to play a role in minimizing threats to the human security dimension in Lebanon.